2007
DOI: 10.1128/jvi.00844-07
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Brome Mosaic Virus RNAs and Cytoplasmic Processing Bodies

Abstract: Cytoplasmic processing bodies are sites where nontranslating mRNAs accumulate for different fates, including decapping and degradation, storage, or returning to translation. Previous work has also shown that the Lsm1-7p complex, Dhh1p, and Pat1p, which are all components of P bodies, are required for translation and subsequent recruitment to replication of the plant virus brome mosaic virus (BMV) genomic RNAs when replication is reproduced in yeast cells. To better understand the role of P bodies in BMV replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 44 publications
2
50
0
1
Order By: Relevance
“…P-bodies may also be assembly sites for a BMV replication complex that functions in S. cerevisiae, because Pbody components are required for BMV genomic RNA translation (22,33,47) and sequester translationally repressed BMV RNA1 and RNA2 (4). The size of P-body foci changes according to the rate of mRNA decapping in the cell.…”
Section: Discussionmentioning
confidence: 99%
“…P-bodies may also be assembly sites for a BMV replication complex that functions in S. cerevisiae, because Pbody components are required for BMV genomic RNA translation (22,33,47) and sequester translationally repressed BMV RNA1 and RNA2 (4). The size of P-body foci changes according to the rate of mRNA decapping in the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Their components are required for efficient RTP of yeast Ty elements and for the translation and subsequent recruitment to replication of BMV (2,33,36). These studies suggested that P bodies are subcellular foci where viral genomic RNAs (gRNAs) and proteins aggregate to facilitate their assembly and replication.…”
Section: Discussionmentioning
confidence: 99%
“…In the yeast Saccharomyces cerevisiae, virus-like particle formation and retrotransposition of the Ty1 and Ty3 retrotransposons are dependent upon the P-body components Dhh1p/DDX6, Lsm1p, and PatL1p (8,18,31). Similarly, several P-body proteins promote the translation and replication of the plant RNA virus brome mosaic virus (BMV) (6,29,71,80). Conversely, P-body components have also been shown to be inhibitory to some viruses and retroelements.…”
mentioning
confidence: 99%